LncRNA MALAT‐1 Elevates HMGB1 to Promote Autophagy Resulting in Inhibition of Tumor Cell Apoptosis in Multiple Myeloma. Issue 10 (3rd May 2017) - Gao, Da; Lv, Ai‐e; Li, Hui‐Ping; Han, Dong‐Hai; Zhang, Ya‐Peng
ABSTRACT: Long non‐coding RNAs (lncRNAs) can participate in the pathological process of multiple myeloma (MM) via regulation of specific gene expression and function. This research aimed to study the role of MALAT‐1 and the underlying mechanism in MM. In this study, the expression of MALAT‐1 and HMGB1 protein in the bone marrow mononuclear cells from MM patients at different stages and in MM cell lines was determined by qRT‐PCR and western blot, respectively. The endogenous expression of MALAT‐1 and HMGB1 was modulated using lentivirus vectors transfection. CHX chase assay and RIP analyses were performed to explore the interaction between MALAT‐1 and HMGB1 in MM. Nude mouse xenograft was made and used for in vivo experiment study. The expression of MALAT‐1 and HMGB1 in the bone marrow mononuclear cells from patients with untreated multiple myeloma was dramatically increased, as well as in MM cell lines, KM3 and U266; while MALAT‐1 expression and HMGB1 protein level both decreased significantly in complete remission patients. Furthermore, MALAT‐1 knockdown facilitated the degradation of HMGB1 at the post‐translational level via increase of the ubiquitination of HMGB1 in MM cells. MALAT‐1 was shown to promote autophagy in MM through upregulation of HMGB1. In vivo, MALAT‐1 knockdown could inhibit tumor growth significantly in tumor‐bearing mice and reduced the protein expressions of HMGB1, Beclin‐1, and LC3B in tumor tissues. LncRNA MALAT‐1 increases the expression level of HMGB1 in MM thereby promotes autophagy resulting in the inhibition of apoptosis. J. Cell. Biochem. 118: 3341–3348, 2017. © 2017 Wiley Periodicals, Inc. Abstract : We explored the involvement of MALAT‐1 in multiple myeloma (MM) and the correlated mechanism in vitro and in vivo. MALAT‐1 highly expressed in MM and inhibited tumor cell apoptosis. MALAT‐1 could promote MM cell autophagy via regulation of HMGB1 at the post‐translational level.